2005
DOI: 10.1002/ejic.200400576
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Oxovanadium(IV) to Dipeptides Containing Histidine and Cysteine Residues

Abstract: The complexation of the oxovanadium(IV) ion with five dipeptides containing L-histidine or L-cysteine (GlyHis, HisHis, HisGly, CysGly, GlyCys) was studied. L-histidinamide (HisNH 2 ) was assumed as a model system for dipeptides with L-histidine in the N-terminal position. The study was performed in aqueous solution through the combined application of potentiometric and spectroscopic (electronic absorption and EPR) techniques. The results indicate that simple dipeptides lacking a strong anchoring group can form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
68
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 60 publications
16
68
0
Order By: Relevance
“…[15] The value of A z predicted by the "additivity rule" is 159 ϫ 10 O ion is -1 (VOLH -1 ) and -2 (VOLH -2 ), respectively. [13] The two expected values are significantly higher than those measured: as discussed later, it is possible to predict the A z value for the two species also by DFT methods, which give results comparable with those experimentally measured. However, by following what was done by Saladino and Larsen [31] for V IV O imidazole species after the fundamental work of Pecoraro and co-workers, [32] we studied through DFT calculations the value of 51 V A z in V…”
Section: ͻ1supporting
confidence: 54%
See 2 more Smart Citations
“…[15] The value of A z predicted by the "additivity rule" is 159 ϫ 10 O ion is -1 (VOLH -1 ) and -2 (VOLH -2 ), respectively. [13] The two expected values are significantly higher than those measured: as discussed later, it is possible to predict the A z value for the two species also by DFT methods, which give results comparable with those experimentally measured. However, by following what was done by Saladino and Larsen [31] for V IV O imidazole species after the fundamental work of Pecoraro and co-workers, [32] we studied through DFT calculations the value of 51 V A z in V…”
Section: ͻ1supporting
confidence: 54%
“…[11] Recently the role of the anchoring groups was studied with V IV O and it was found that phenolate O -, alcoholate O -, thiolate S -, carboxylate COO -, amino NH 2 , and imidazole N are effective in promoting peptide amide deprotonation and coordination. [12,13] Many examples of V IV O complexes containing a V-N -(amide) bond, both in solution and in the solid state, were characterized over the last years in the literature. [12][13][14] We recently demonstrated that the di(imidazol-2-yl) residue behaves as a good anchoring group, avoiding the hydrolysis and precipitation of vanadium hydroxide and allowing for the coordination of the amide nitrogen-N -.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…catalysis, insulin-enhancing, anti-tumor) of already known compounds. For example: Schiff bases of the salen-type (66), reduced Schiff bases of salan-type (171,172,173), sal-amino acidate and other Schiff bases, including the reducedtype derivatives, (28,78,193,195,197,216,217), amino acids or peptides (186)(187)(188)(189)196), hydroxycarboxylates (198,218,219,221) 158,180,184,[224][225][226][227][228][229][230][231][232][233][234].…”
Section: Coordination Chemistrymentioning
confidence: 99%
“…19,66,[171][172][173][174][175][176], pyrone, pyridinone and pyrimidinone complexes (177)(178)(179), several types of Schiff bases and related complexes (66, [180][181][182], picolinato (e.g. 183), quinoline derivatives (184) dipicolinato complexes (185), compounds involving ligands such as amino acids or derivatives (28,(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196)(197), hydroxycarboxylates (198,199), but novel classes of coordination compounds and other new reports on previously known compounds are too many to name.…”
Section: Coordination Chemistrymentioning
confidence: 99%